PROFIL DE LA POPULATION AGEE CONSUMATRICE DE MEDICAMENTS GENERIQUES ET SES REPRESENTATIONS SOCIALES (Fiep Bulletin - online, 2012)
The present study unveiled a profile of the elderly population of the city of João Pessoa which presents a significant percentage of women aged 60 to 65 years with a minimum wage income. In general, the social representations of generic drugs produced by these seniors had a positive connotation to the word bind price. The elderly were positioned negatively portray the question of effectiveness of generic drugs to be distributed for free.Understanding this reality common to all social dubious presented here allowed us to capture some thoroughness prepared by means of perception about the elderly generic and can be used as a foundation for implementation of future strategies to advance the implementation of the policy of generic the elderly population, aiming to increase of adhesion of generic medicines that portion of the population.
Keywords: Elderly; Generic Drugs; Social Representations.